Peanut allergen characterization and allergenicity throughout development - Cohen, Casey G.; Levy, Yael; Toscano-Rivero, Diana; Manasherova, Ekaterina; Agmon-Levin, Nancy; Kenett, Ron S.; Jean-Claude, Bertrand J.; Mazer, Bruce D.; Hovav, Ran; Kidon, Mona I. (Frontiers in Allergy, 2024)
IntroductionPeanut allergy (PA) in children is a major concern. There is a need for better biological material for both diagnosis and oral immunotherapy (OIT) treatments. The unique state of seeds at early reproductive stages may affect the allergenicity of storage proteins, and impact clinical diagnostic and OIT protocols. The objective of this study was to evaluate the major allergen content in sequential seed developmental stages and monitor allergenicity via specific IgE binding quantification and skin prick testing.MethodsSeeds were collected from peanut plants and sorted into five developmental stages: initial (S1), developing (S2), full-size without coloration (S3), full-size with coloration (S4), and fully mature (S5) seeds. Samples were characterized by RNA-Seq, ELISA, and immunohistochemistry. Lyophilized, ground preparations were used for evaluation of skin test responses in sixty challenge-proven PA children.ResultsGene expression, protein content, and specific IgE binding of allergenic proteins increased throughout seed maturation and development. An expression bias towards the less allergenic A-genome copy of the major allergen Ara h 2 was found in earlier stages, especially in stage S2. Immunohistochemical staining showed that Ara h 2 is more dispersed in the cell and less accumulated within organized bodies at stage S2 versus stage S4. Significant differences were found in mean wheal responses between the commercial peanut extract (equivalent to stage S5) and stages S1 and S2, but not with stage S4, upon skin prick testing in subjects with PA.DiscussionThe observed decrease in peanut-specific IgE binding of immature peanut seeds may be a result not only of decreased amounts of allergenic proteins, but also of profound changes in seed composition and conformation. This may be significant for developing a safer and more effective peanut OIT protocol.